2009
DOI: 10.1016/j.neuroimage.2009.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Brain networks underlying perceptual habituation to repeated aversive visceral stimuli in patients with irritable bowel syndrome

Abstract: Patients with irritable bowel syndrome (IBS) show decreased discomfort and pain thresholds to visceral stimuli, as well hypervigilance to gastrointestinal sensations, symptoms, and the context in which these visceral sensations and symptoms occur. Previous research demonstrated normalization of visceral hypersensitivity following repeated exposure to experimental rectal stimuli over a 12 month period that was associated with reduction in cortical regions functionally associated with attention and arousal. Buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 62 publications
4
55
1
1
Order By: Relevance
“…Hence, the changes in the monoaminergic system in amygdala due to eugenol pretreatment in RS rats could be due to reduced corticosterone level. Neuropathological studies suggest that the emotional arousal circuitry which plays an important role in IBS is inhibited by PFC (Labus et al, 2009). Therefore, we may presume that the neuroprotective effect of eugenol in RS-induced gastrointestinal dysfunction may be due to region-specific action of eugenol in PFC and amygdala which is, however, subject to further experimentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the changes in the monoaminergic system in amygdala due to eugenol pretreatment in RS rats could be due to reduced corticosterone level. Neuropathological studies suggest that the emotional arousal circuitry which plays an important role in IBS is inhibited by PFC (Labus et al, 2009). Therefore, we may presume that the neuroprotective effect of eugenol in RS-induced gastrointestinal dysfunction may be due to region-specific action of eugenol in PFC and amygdala which is, however, subject to further experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, centrally acting drugs such as selective serotonin reuptake inhibitors (SSRI's) have been shown to be effective in the treatment of IBS (Ford et al, 2009). Experimental studies on models exhibiting IBS symptoms have shown the engagement of emotional arousal circuitry which includes limbic regions such as hippocampus, hypothalamus, pre-frontal cortex (PFC), and amygdala (Labus et al, 2009). Hypothalamicpituitary-adrenal cortex (HPA)-axis is the key component of stress response which is regulated by higher limbic brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…This not only shows the sensitivity of evoked potentials to reflect subtle changes in sensitivity over time but also highlights the importance of factoring in habituation into experimental protocols that use repeated measures to determine outcomes. The fact that habituation to pain is often absent or reduced in patients with functional pain syndromes makes this an important observation to consider in future studies (19,36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, with identical rectal stimulus intensity, brain activation in the early pain processing areas was greater in IBS than in controls whereas, in subjective rating-matched stimulation, there were only minor activation differences in these areas between subject groups 45 118. Several recent interesting studies have examined the linkage between the main pain processing centres in IBS using connectivity analysis 108 119 120. However, owing to the absence of adequate control groups, they can only provide indirect evidence of any disease-related changes in modulation and will not be considered here.…”
Section: Endogenous Pain Modulation (Epm) In Fgidsmentioning
confidence: 99%